Composite preparation for curing fluorine and phosphorus in ardealite and application thereof
Through the synergistic efficiency method of modified clay minerals and clay minerals, a three-dimensional structure with high porosity and high specific surface area is formed, which solves the problem of low fluorine and phosphorus removal efficiency in phosphogypsum in the prior art, and achieves a more efficient removal effect.
Patent Information
- Application Number
- CN202510207920.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the composite preparations used to cure fluorine and phosphorus in phosphogypsum have low recovery efficiency, and it is difficult to effectively remove phosphorus and fluorine in phosphogypsum.
The synergistic efficiency method of modified clay minerals and clay minerals is adopted to form a three-dimensional structure with large porosity, large specific surface area and high surfactant content through the preparation process of modified clay minerals, so as to maximize the adsorption of phosphorus and fluorine in phosphogypsum.
The removal rate of phosphorus and fluorine in phosphogypsum is significantly improved, and the modified clay minerals form bonds with fluorine and phosphorus in the system, increasing the contact area, and achieving a more efficient removal effect.
Abstract
Description
Technical Field
[0001] The invention relates to the field of phosphogypsum processing, and in particular to a composite preparation of fluorine and phosphorus for solidifying phosphogypsum and application thereof. Background Art
[0002] Phosphogypsum refers to the industrial solid waste residue produced when phosphate ore is treated with sulfuric acid to produce phosphoric acid. The main component is calcium sulfate dihydrate. Phosphogypsum contains a variety of harmful impurities, including phosphorus, fluorine and organic matter. The presence of phosphorus and fluorine in phosphogypsum will affect the application properties of the hardened body strength and setting time of phosphogypsum, hindering the resource utilization of phosphogypsum. Therefore, the removal of phosphorus and fluorine impurities in phosphogypsum is the key to its resource utilization. In addition, the stockpile of phosphogypsum is huge, and harmless treatment will bring huge economic benefits. In industry, the lime neutralization method can be used to solidify the soluble phosphorus and soluble fluorine in phosphogypsum to achieve its harmless treatment.
[0003] The solidification of soluble phosphorus and soluble fluorine in phosphogypsum by lime neutralization involves a traditional chemical reaction: first, lime reacts with an aqueous solution to form a calcium hydroxide suspension, and at the same time, the soluble phosphorus and soluble fluorine in the phosphogypsum are dissolved in the aqueous solution and the calcium hydroxide suspension to form Ca3(PO4)2 and CaF2 insoluble precipitates, respectively, thereby achieving harmless treatment of the phosphogypsum. A Chinese invention patent with publication number CN115784238B discloses a method for recovering soluble fluorine in phosphogypsum. The invention comprises heating a phosphogypsum decomposer, adding solid phosphogypsum and a phosphogypsum decomposition accelerator, and heating the mixture at a constant temperature. After stirring the reaction, the mixture is filtered while hot, and the filtrate is transferred to a container and a metal ion stabilizer is added, and then a fluorine conversion agent is added. At the same time, air is continuously blown into the filtrate, and the gas phase escaping from the flask is discharged into the atmosphere after passing through a washing bottle filled with clean water. After the reaction, the liquid in the flask is evaporated and crystallized, and the escaping gas phase is washed with the same washing bottle. After the crystallization is completed, the filtrate and gypsum crystals with low impurity content are obtained by filtering. The filtrate is returned for use as a circulating liquid, and the liquid obtained in the washing bottle is a fluorosilicic acid solution. Although this method achieves purification and impurity removal in the process of fluorine recovery of phosphogypsum, the fluorine removal and phosphorus removal efficiency of this method are relatively low.
[0004] Therefore, according to the above-mentioned related technologies, it is urgent to develop a composite preparation of fluorine and phosphorus for solidifying phosphogypsum and its application. Summary of the invention
[0005] In view of this, the object of the present invention is to propose a composite formulation of fluorine and phosphorus for solidifying phosphogypsum and its application, so as to solve the problem of low recovery efficiency of the composite formulation of fluorine and phosphorus for solidifying phosphogypsum in the prior art.
[0006] Based on the above purpose, the present invention provides a composite preparation of fluorine and phosphorus for solidifying phosphogypsum and its application.
[0007] A composite preparation for solidifying fluorine and phosphorus in phosphogypsum, comprising the following raw materials in parts by weight: 20-40 parts of modified clay mineral, 10-15 parts of clay mineral, 1-2 parts of coagulant, 0.1-0.6 parts of additive, 180-200 parts of deionized water, and 1.55-5.7 parts of fly ash;
[0008] The modified clay mineral is a mixed clay mineral modified by hydroxy iron;
[0009] The mixed clay mineral is obtained by mixing a clay mineral grafted with maleic anhydride and a clay mineral grafted with polyacrylic acid-sodium acrylate;
[0010] The clay mineral is any one of montmorillonite, bentonite, diatomaceous earth, kaolinite, attapulgite and loess;
[0011] The coagulant is any one of PAC-26% and PAC-98%;
[0012] The auxiliary agent is a calcium hydroxide solution with a concentration of 1-2wt%.
[0013] Preferably, the preparation method of the modified clay mineral is as follows:
[0014] Step S1. adding clay mineral to HCl solution, stirring at 75-80°C for 30-50 min, cooling to room temperature after the reaction is completed, filtering, washing with single distilled water until neutral, and drying to obtain a mixture A;
[0015] Step S2. Mix the mixture A, primary distilled water and anhydrous ethanol, stir and disperse for 25-35 minutes, adjust the pH of the system to 3-4, then add KH-570, continue to stir and react for 25-35 minutes at room temperature, then adjust the pH of the system to 9-10, heat to 75-80°C, stir and react for 2-3 hours, and after the reaction is completed, filter the product, wash with ethanol 2-3 times, and then dry at 45-50°C for 5 hours to obtain a mixture B;
[0016] Step S3. Mix the mixture B and 1,4-dioxane evenly, stir and disperse for 50-60 minutes, add N-vinyl pyrrolidone, maleic anhydride and N'N-methylenebisacrylamide in sequence, continue stirring for 50-60 minutes, then add azobisisobutyronitrile, react at 70-75°C for 3.5-4 hours, then add NaOH solution, stir for 1 hour, filter, wash with distilled water once until neutral, wash with anhydrous acetone 2-3 times, and vacuum dry for 6-7 hours to obtain a clay mineral grafted with maleic anhydride;
[0017] Step S4. Cyclohexane and emulsifier Span80 are stirred electrically at 40-45° C. and 225-250 r / min for 25-35 min to obtain a mixture C;
[0018] Step S5. Dissolve NaOH in deionized water, add acrylic acid, clay mineral and N'N-methylenebisacrylamide, stir electrically at 475-500 r / min for 50-60 min, and then add potassium persulfate to obtain a mixture D;
[0019] Step S6. The mixture C is heated to 65-70° C., the mixture D is added dropwise to the mixture C, stirred at a speed of 475-500 r / min for 2-3 hours, filtered, washed with distilled water for 2-3 times, and then dried in a constant temperature drying oven at 125-150° C. for 5-6 hours to obtain a polyacrylic acid-sodium acrylate grafted clay mineral;
[0020] Step S7. Add NaOH solution to FeCl3 solution, stir for 1.5-2h, add maleic anhydride grafted clay mineral and polyacrylic acid-sodium acrylate grafted clay mineral, stir for 2-3h, filter and separate the solid phase product, wash with distilled water until there is no chloride ion in the filtrate, and then dry at 125-150°C for 5-6h to obtain a modified clay mineral.
[0021] Preferably, the clay mineral in step S1 is a clay mineral that has passed through a 100-mesh sieve, the usage ratio of the clay mineral to the HCl solution is 8-13 g:90-110 mL, and the concentration of the HCl solution is 20%-30%.
[0022] Preferably, in step S2, the ratio of the mixture A, single distilled water, anhydrous ethanol and KH-570 is 8-13 g: 40-50 mL: 30-40 mL: 4-9 g.
[0023] Preferably, in step S3, the dosage ratio of the mixture B, 1,4-dioxane, N-vinyl pyrrolidone, maleic anhydride, N'N-methylenebisacrylamide, azobisisobutyronitrile and NaOH solution is 15-20 g: 150-160 mL: 10-15 g: 10-15 g: 2-3 g: 8-10 g: 10-15 mL, and the concentration of the NaOH solution is 20%-30%.
[0024] Preferably, the usage ratio of cyclohexane and emulsifier Span80 in step S4 is 50-55 mL: 2-3 mL.
[0025] Preferably, in step S5, the dosage ratio of NaOH, deionized water, acrylic acid, clay mineral, N'N-methylenebisacrylamide and potassium persulfate is 0.2-0.25 g: 12-17 mL: 1.5-2.5 mL: 5-10 g: 0.2-0.3 g: 0.05-0.1 g, and the clay mineral is a clay mineral passed through a 100 mesh sieve.
[0026] Preferably, in step S6, the usage ratio of mixture C to mixture D is 50-55 mL:15-20 mL.
[0027] Preferably, in step S7, the dosage ratio of the NaOH solution, the FeCl3 solution, the maleic anhydride grafted clay mineral and the polyacrylic acid-sodium acrylate grafted clay mineral is 460-500 mL: 140-160 mL: 17-22 g: 30-35 g, the concentration of the NaOH solution is 0.25-0.35 mol / L, and the concentration of the FeCl3 solution is 0.07-0.12 mol / L.
[0028] The invention discloses an application of a composite preparation for solidifying fluorine and phosphorus in phosphogypsum. The composite preparation is used for solidifying fluorine and phosphorus in phosphogypsum.
[0029] Beneficial effects of the present invention:
[0030] The composite preparation provided by the present invention can greatly increase the removal rate of fluorine and phosphorus in phosphogypsum, wherein the modified clay mineral and the clay mineral synergistically enhance the efficiency, and can form a three-dimensional structure with large porosity, large specific surface area and large content of surface active groups inside the system, which can maximize the adsorption of phosphorus and fluorine in phosphogypsum and has broad application prospects.
[0031] The modified clay mineral provided by the present invention has a larger adsorption capacity and its surface can also form bonds with a large amount of fluorine and phosphorus in the system. In addition, the unmodified clay mineral is compounded to make the system more evenly dispersed, which increases the contact area between the composite preparation and the fluorine and phosphorus in the system, and further increases the removal rate of fluorine and phosphorus. DETAILED DESCRIPTION
[0032] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0033] In the following examples and comparative examples, the specific composition of the clay minerals used is shown in the following table:
[0034] Kaolin <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[P2O5]]> <![CDATA[Na2O]]> MgO <![CDATA[K2O]]> CaO <![CDATA[Fe2O3]]> Content (wt%) 50.41 42.63 0.091 0.055 0.046 0.032 0.013 0.011
[0035] Example 1: A method for preparing a composite preparation of fluorine and phosphorus for solidifying phosphogypsum, comprising the following steps:
[0036] Step S1. 8 g of clay mineral passed through a 100-mesh sieve was added to 90 mL of a 20% HCl solution, and stirred at 75° C. for 30 min. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with distilled water until neutral, and dried to obtain a mixture A;
[0037] Step S2. 8 g of mixture A, 40 mL of primary distilled water and 30 mL of anhydrous ethanol were mixed, stirred and dispersed for 25 min, the pH of the system was adjusted to 3, and then 4 g of KH-570 was added, and the reaction was continued at room temperature for 25 min with stirring, and then the pH of the system was adjusted to 9, the temperature was raised to 75 ° C, and the reaction was stirred for 2 h. After the reaction was completed, the product was filtered, washed twice with ethanol, and then dried at 45 ° C for 5 h to obtain a mixture B;
[0038] Step S3. 15 g of mixture B and 150 mL of 1,4-dioxane were mixed evenly, stirred and dispersed for 50 min, 10 g of N-vinyl pyrrolidone, 10 g of maleic anhydride and 2 g of N'N-methylenebisacrylamide were added in sequence, stirring was continued for 50 min, 8 g of azobisisobutyronitrile was added, the mixture was reacted at 70 ° C for 3.5 h, 10 mL of NaOH solution was added, and after stirring for 1 h, the mixture was filtered, washed with distilled water once until neutral, washed twice with anhydrous acetone, and vacuum dried for 6 h to obtain a clay mineral grafted with maleic anhydride;
[0039] Step S4. 50 g of cyclohexane and 2 mL of emulsifier Span80 were stirred electrically at 40° C. and 225 r / min for 25 min to obtain a mixture C;
[0040] Step S5. 0.2 g of NaOH was dissolved in 12 mL of deionized water, 1.5 mL of acrylic acid, 5 g of clay mineral passed through a 100-mesh sieve and 0.2 g of N'N-methylenebisacrylamide were added, the mixture was stirred at 475 r / min for 50 min, and 0.05 g of potassium persulfate was added to obtain a mixture D;
[0041] Step S6. The mixture C is heated to 65° C., 15 mL of the mixture D is added dropwise to 50 mL of the mixture C, stirred at a speed of 475 r / min for 2 h, filtered, washed twice with distilled water, and then dried in a constant temperature drying oven at 125° C. for 5 h to obtain a polyacrylic acid-sodium acrylate grafted clay mineral;
[0042] Step S7. Add 460 mL of a 0.25 mol / L NaOH solution to 140 mL of a 0.07 mol / L FeCl3 solution, stir for 1.5 h, add 17 g of a maleic anhydride grafted clay mineral and 30 g of a polyacrylic acid-sodium acrylate grafted clay mineral, stir for 2 h, filter and separate the solid phase product, wash with distilled water until there is no chloride ion in the filtrate, and then dry at 125 ° C for 5 h to obtain a modified clay mineral;
[0043] Step S8. 20 g of modified clay mineral, 10 g of clay mineral passed through a 100-mesh sieve, 1 g of PAC-26%, 0.1 g of 1% calcium hydroxide solution, 180 g of deionized water and 1.55 g of fly ash are mixed and stirred to obtain a composite preparation.
[0044] Example 2: A method for preparing a composite preparation of fluorine and phosphorus for solidifying phosphogypsum, comprising the following steps:
[0045] Step S1. 9 g of clay mineral passed through a 100-mesh sieve was added to 94 mL of a 22% HCl solution, and stirred at 76° C. for 34 min. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with distilled water until neutral, and dried to obtain a mixture A;
[0046] Step S2. 9 g of mixture A, 42 mL of primary distilled water and 32 mL of anhydrous ethanol were mixed, stirred and dispersed for 27 min, the pH of the system was adjusted to 3, and then 5 g of KH-570 was added, and the reaction was continued at room temperature for 27 min with stirring, and then the pH of the system was adjusted to 9, the temperature was raised to 76 ° C, and the reaction was stirred for 2 h. After the reaction was completed, the product was filtered, washed twice with ethanol, and then dried at 46 ° C for 5 h to obtain mixture B;
[0047] Step S3. 16 g of mixture B and 152 mL of 1,4-dioxane were mixed evenly, stirred and dispersed for 52 min, 11 g of N-vinyl pyrrolidone, 11 g of maleic anhydride and 2.2 g of N'N-methylenebisacrylamide were added in sequence, stirring was continued for 52 min, 8.4 g of azobisisobutyronitrile was added, the mixture was reacted at 71 ° C for 3.6 h, 11 mL of NaOH solution was added, stirred for 1 h, filtered, washed with distilled water once until neutral, washed twice with anhydrous acetone, and vacuum dried for 6 h to obtain a clay mineral grafted with maleic anhydride;
[0048] Step S4. 51 g of cyclohexane and 2.2 mL of emulsifier Span80 were stirred electrically at 41° C. and 230 r / min for 27 min to obtain a mixture C;
[0049] Step S5. 0.21 g of NaOH was dissolved in 13 mL of deionized water, 1.7 mL of acrylic acid, 6 g of clay mineral passed through a 100-mesh sieve and 0.22 g of N'N-methylenebisacrylamide were added, the mixture was stirred at 480 r / min for 52 min, and 0.06 g of potassium persulfate was added to obtain a mixture D;
[0050] Step S6. The mixture C is heated to 66° C., 16 mL of the mixture D is added dropwise to 51 mL of the mixture C, stirred at a speed of 480 r / min for 2 h, filtered, washed twice with distilled water, and then dried in a constant temperature drying oven at 130° C. for 5 h to obtain a polyacrylic acid-sodium acrylate grafted clay mineral;
[0051] Step S7. Add 468 mL of a 0.27 mol / L NaOH solution to 144 mL of a 0.08 mol / L FeCl3 solution, stir for 1.6 h, add 18 g of a maleic anhydride-grafted clay mineral and 31 g of a polyacrylic acid-sodium acrylate-grafted clay mineral, stir for 2 h, filter and separate the solid phase product, wash with distilled water until there is no chloride ion in the filtrate, and then dry at 130 ° C for 5 h to obtain a modified clay mineral;
[0052] Step S8. 24 g of modified clay mineral, 11 g of clay mineral passed through a 100-mesh sieve, 1 g of PAC-98%, 0.2 g of a 1% calcium hydroxide solution, 184 g of deionized water and 2.5 g of fly ash are mixed and stirred to obtain a composite preparation.
[0053] Example 3: A method for preparing a composite preparation of fluorine and phosphorus for solidifying phosphogypsum, comprising the following steps:
[0054] Step S1. 10 g of clay mineral passed through a 100-mesh sieve was added to 98 mL of a 24% HCl solution, and stirred at 77° C. for 38 min. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with distilled water until neutral, and dried to obtain a mixture A;
[0055] Step S2. 10 g of mixture A, 44 mL of primary distilled water and 34 mL of anhydrous ethanol were mixed, stirred and dispersed for 29 min, the pH of the system was adjusted to 3, and then 6 g of KH-570 was added, and the reaction was continued at room temperature for 29 min with stirring, and then the pH of the system was adjusted to 9, the temperature was raised to 77 ° C, and the reaction was stirred for 2 h. After the reaction was completed, the product was filtered, washed twice with ethanol, and then dried at 47 ° C for 5 h to obtain a mixture B;
[0056] Step S3. 17 g of mixture B and 154 mL of 1,4-dioxane were mixed evenly, and the mixture was stirred and dispersed for 54 min. 12 g of N-vinyl pyrrolidone, 12 g of maleic anhydride and 2.4 g of N'N-methylenebisacrylamide were added in sequence, and the stirring was continued for 54 min. Then 8.8 g of azobisisobutyronitrile was added, and the mixture was reacted at 72 ° C for 3.7 h. Then 12 mL of NaOH solution was added, and the mixture was stirred for 1 h, and then filtered, washed with distilled water once until neutral, washed with anhydrous acetone twice, and vacuum dried for 6 h to obtain a clay mineral grafted with maleic anhydride;
[0057] Step S4. 52 g of cyclohexane and 2.4 mL of emulsifier Span80 were stirred electrically at 42° C. and 235 r / min for 29 min to obtain a mixture C;
[0058] Step S5. 0.22 g of NaOH was dissolved in 14 mL of deionized water, 1.9 mL of acrylic acid, 7 g of clay mineral passed through a 100-mesh sieve and 0.24 g of N'N-methylenebisacrylamide were added, the mixture was stirred at 485 r / min for 54 min, and 0.07 g of potassium persulfate was added to obtain a mixture D;
[0059] Step S6. The mixture C is heated to 67° C., 17 mL of the mixture D is added dropwise to 52 mL of the mixture C, stirred at a speed of 485 r / min for 2 h, filtered, washed twice with distilled water, and then dried in a constant temperature drying oven at 135° C. for 5 h to obtain a polyacrylic acid-sodium acrylate grafted clay mineral;
[0060] Step S7. Add 476 mL of a 0.29 mol / L NaOH solution to 148 mL of a 0.09 mol / L FeCl3 solution, stir for 1.7 h, add 19 g of a maleic anhydride grafted clay mineral and 32 g of a polyacrylic acid-sodium acrylate grafted clay mineral, stir for 2 h, filter and separate the solid phase product, wash with distilled water until there is no chloride ion in the filtrate, and then dry at 135 ° C for 5 h to obtain a modified clay mineral;
[0061] Step S8. 28 g of modified clay mineral, 12 g of clay mineral passed through a 100-mesh sieve, 1 g of PAC-26%, 0.3 g of a 1% calcium hydroxide solution, 188 g of deionized water and 3.5 g of fly ash are mixed and stirred evenly to obtain a composite preparation.
[0062] Example 4: A method for preparing a composite preparation of fluorine and phosphorus for solidifying phosphogypsum, comprising the following steps:
[0063] Step S1. 11 g of clay mineral passed through a 100-mesh sieve was added to 102 mL of a 26% HCl solution, and the mixture was stirred at 78° C. for 42 min. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with distilled water until neutral, and dried to obtain a mixture A;
[0064] Step S2. 11 g of mixture A, 46 mL of primary distilled water and 36 mL of anhydrous ethanol were mixed, stirred and dispersed for 31 min, the pH of the system was adjusted to 4, and then 7 g of KH-570 was added, and the reaction was continued at room temperature for 31 min with stirring, and then the pH of the system was adjusted to 10, the temperature was raised to 78 ° C, and the reaction was stirred for 3 h. After the reaction was completed, the product was filtered, washed with ethanol 3 times, and then dried at 48 ° C for 5 h to obtain mixture B;
[0065] Step S3. 18 g of mixture B and 156 mL of 1,4-dioxane were mixed evenly, and the mixture was stirred and dispersed for 56 min. 13 g of N-vinyl pyrrolidone, 13 g of maleic anhydride and 2.6 g of N'N-methylenebisacrylamide were added in sequence, and the stirring was continued for 56 min. 9.2 g of azobisisobutyronitrile was added, and the mixture was reacted at 73 ° C for 3.8 h. 13 mL of NaOH solution was added, and the mixture was stirred for 1 h, and then filtered, washed with distilled water once until neutral, washed with anhydrous acetone for 3 times, and vacuum dried for 7 h to obtain a clay mineral grafted with maleic anhydride;
[0066] Step S4. 53 g of cyclohexane and 2.6 mL of emulsifier Span80 were stirred electrically at 43° C. and 240 r / min for 31 min to obtain a mixture C;
[0067] Step S5. 0.23 g of NaOH was dissolved in 15 mL of deionized water, 2.1 mL of acrylic acid, 8 g of clay mineral passed through a 100-mesh sieve and 0.26 g of N'N-methylenebisacrylamide were added, the mixture was stirred at 490 r / min for 56 min, and 0.08 g of potassium persulfate was added to obtain a mixture D;
[0068] Step S6. The mixture C is heated to 68° C., 18 mL of the mixture D is added dropwise to 53 mL of the mixture C, stirred at a speed of 490 r / min for 3 h, filtered, washed with distilled water for 3 times, and then dried in a constant temperature drying oven at 140° C. for 6 h to obtain a polyacrylic acid-sodium acrylate grafted clay mineral;
[0069] Step S7. Add 484 mL of a 0.31 mol / L NaOH solution to 152 mL of a 0.1 mol / L FeCl3 solution, stir for 1.8 h, add 20 g of a maleic anhydride grafted clay mineral and 33 g of a polyacrylic acid-sodium acrylate grafted clay mineral, stir for 3 h, filter and separate the solid phase product, wash with distilled water until there is no chloride ion in the filtrate, and then dry at 140 ° C for 6 h to obtain a modified clay mineral;
[0070] Step S8. 32 g of modified clay mineral, 13 g of clay mineral passed through a 100-mesh sieve, 2 g of PAC-98%, 0.4 g of a 2% calcium hydroxide solution and 192 g of deionized water were mixed and stirred to obtain a composite preparation.
[0071] Example 5: A method for preparing a composite preparation of fluorine and phosphorus for solidifying phosphogypsum, comprising the following steps:
[0072] Step S1. 12 g of clay mineral passed through a 100-mesh sieve was added to 106 mL of a 28% HCl solution, and the mixture was stirred at 79° C. for 46 min. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with distilled water until neutral, and dried to obtain a mixture A;
[0073] Step S2. 12 g of mixture A, 48 mL of primary distilled water and 38 mL of anhydrous ethanol were mixed, stirred and dispersed for 33 min, the pH of the system was adjusted to 4, and then 8 g of KH-570 was added, and the reaction was continued at room temperature for 33 min with stirring, and then the pH of the system was adjusted to 10, the temperature was raised to 79 ° C, and the reaction was stirred for 3 h. After the reaction was completed, the product was filtered, washed with ethanol 3 times, and then dried at 49 ° C for 5 h to obtain a mixture B;
[0074] Step S3. 19 g of mixture B and 158 mL of 1,4-dioxane were mixed evenly, stirred and dispersed for 58 min, 14 g of N-vinyl pyrrolidone, 14 g of maleic anhydride and 2.8 g of N'N-methylenebisacrylamide were added in sequence, stirring was continued for 58 min, 9.6 g of azobisisobutyronitrile was added, the mixture was reacted at 74 ° C for 3.9 h, 14 mL of NaOH solution was added, and after stirring for 1 h, the mixture was filtered, washed with distilled water once until neutral, washed with anhydrous acetone for 3 times, and vacuum dried for 7 h to obtain a clay mineral grafted with maleic anhydride;
[0075] Step S4. 54 g of cyclohexane and 2.8 mL of emulsifier Span80 were stirred electrically at 44° C. and 245 r / min for 33 min to obtain a mixture C;
[0076] Step S5. 0.24 g of NaOH was dissolved in 16 mL of deionized water, 2.3 mL of acrylic acid, 9 g of clay mineral passed through a 100-mesh sieve and 0.28 g of N'N-methylenebisacrylamide were added, the mixture was stirred at 495 r / min for 58 min, and 0.09 g of potassium persulfate was added to obtain a mixture D;
[0077] Step S6. The mixture C is heated to 69° C., 19 mL of the mixture D is added dropwise to 54 mL of the mixture C, stirred at a speed of 495 r / min for 3 h, filtered, washed with distilled water for 3 times, and then dried in a constant temperature drying oven at 145° C. for 6 h to obtain a polyacrylic acid-sodium acrylate grafted clay mineral;
[0078] Step S7. Add 492 mL of a 0.33 mol / L NaOH solution to 156 mL of a 0.11 mol / L FeCl3 solution, stir for 1.9 h, add 21 g of a maleic anhydride grafted clay mineral and 34 g of a polyacrylic acid-sodium acrylate grafted clay mineral, stir for 3 h, filter and separate the solid phase product, wash with distilled water until there is no chloride ion in the filtrate, and then dry at 145 ° C for 6 h to obtain a modified clay mineral;
[0079] Step S8. 36 g of modified clay mineral, 14 g of clay mineral passed through a 100-mesh sieve, 2 g of PAC-26%, 0.5 g of a 2% calcium hydroxide solution, 196 g of deionized water and 4.5 g of fly ash were mixed and stirred to obtain a composite preparation.
[0080] Example 6: A method for preparing a composite preparation of fluorine and phosphorus for solidifying phosphogypsum, comprising the following steps:
[0081] Step S1. 13 g of clay mineral passed through a 100-mesh sieve was added to 110 mL of a 30% HCl solution, and stirred at 80° C. for 50 min. After the reaction was completed, the mixture was cooled to room temperature, filtered, washed with distilled water until neutral, and dried to obtain a mixture A;
[0082] Step S2. 13 g of mixture A, 50 mL of primary distilled water and 40 mL of anhydrous ethanol were mixed, stirred and dispersed for 35 min, the pH of the system was adjusted to 4, and then 9 g of KH-570 was added, and the reaction was continued for 35 min at room temperature with stirring, and then the pH of the system was adjusted to 10, the temperature was raised to 80 ° C, and the reaction was stirred for 3 h. After the reaction was completed, the product was filtered, washed with ethanol 3 times, and then dried at 50 ° C for 5 h to obtain a mixture B;
[0083] Step S3. 20 g of mixture B and 160 mL of 1,4-dioxane were mixed evenly, and the mixture was stirred and dispersed for 60 min. 15 g of N-vinyl pyrrolidone, 15 g of maleic anhydride and 3 g of N'N-methylenebisacrylamide were added in sequence, and the stirring was continued for 60 min. Then 10 g of azobisisobutyronitrile was added, and the mixture was reacted at 75 ° C for 4 h. Then 15 mL of NaOH solution was added, and the mixture was stirred for 1 h, and then filtered, washed with distilled water once until neutral, washed with anhydrous acetone for 3 times, and vacuum dried for 7 h to obtain a clay mineral grafted with maleic anhydride;
[0084] Step S4. 55 g of cyclohexane and 3 mL of emulsifier Span80 were stirred electrically at 45° C. and 250 r / min for 35 min to obtain a mixture C;
[0085] Step S5. 0.25 g of NaOH was dissolved in 17 mL of deionized water, 2.5 mL of acrylic acid, 10 g of clay mineral passed through a 100-mesh sieve and 0.3 g of N'N-methylenebisacrylamide were added, the mixture was stirred at 500 r / min for 60 min, and 0.1 g of potassium persulfate was added to obtain a mixture D;
[0086] Step S6. The mixture C is heated to 70° C., 20 mL of the mixture D is added dropwise to 55 mL of the mixture C, stirred at a speed of 500 r / min for 3 h, filtered, washed with distilled water for 3 times, and then dried in a constant temperature drying oven at 150° C. for 6 h to obtain a clay mineral grafted with polyacrylic acid and sodium acrylate;
[0087] Step S7. Add 500 mL of a 0.35 mol / L NaOH solution to 160 mL of a 0.12 mol / L FeCl3 solution, stir for 2 h, add 22 g of a maleic anhydride grafted clay mineral and 35 g of a polyacrylic acid-sodium acrylate grafted clay mineral, stir for 3 h, filter and separate the solid phase product, wash with distilled water until there is no chloride ion in the filtrate, and then dry at 150 ° C for 6 h to obtain a modified clay mineral;
[0088] Step S8. 40 g of modified clay mineral, 15 g of clay mineral passed through a 100-mesh sieve, 2 g of PAC-26% / PAC-98%, 0.6 g of a 2% calcium hydroxide solution, 200 g of deionized water and 5.7 g of fly ash are mixed and stirred evenly to obtain a composite preparation.
[0089] Comparative Example 1:
[0090] Compared with Example 1, this comparative example did not add "modified clay mineral" during the preparation of the composite preparation, and the remaining steps and parameters were the same, which will not be repeated in this comparative example, and finally a composite preparation was obtained.
[0091] Comparative Example 2:
[0092] Compared with Example 1, this comparative example did not add "clay mineral" during the preparation of the composite preparation, and the remaining steps and steps were the same, which will not be repeated in this comparative example, and finally a composite preparation was obtained.
[0093] Comparative Example 3:
[0094] Compared with Example 1, this comparative example only replaces the "clay mineral grafted with maleic anhydride" with "clay mineral grafted with polyacrylic acid-sodium acrylate", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a composite preparation is obtained.
[0095] Comparative Example 4:
[0096] Compared with Example 1, this comparative example only replaces the "polyacrylic acid-sodium acrylate grafted clay mineral" with "maleic anhydride grafted clay mineral", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a composite preparation is obtained.
[0097] Comparative Example 5:
[0098] Compared with Example 1, this comparative example only replaces the "modified clay mineral" with an equal total amount of "clay mineral grafted with maleic anhydride and clay mineral grafted with polyacrylic acid-sodium acrylate", and the remaining steps and parameters are the same, which will not be repeated in this comparative example, and finally a composite preparation is obtained.
[0099] Performance Test:
[0100] Adding the composite preparations prepared in Examples 1 to 6 and Comparative Examples 1 to 5 to the phosphogypsum leachate to test the removal rates of phosphorus and fluorine in the phosphogypsum;
[0101] Determination of phosphate:
[0102] In order to explore the removal ability of the composite preparations prepared in Examples 1 to 6 and Comparative Examples 1 to 5 for phosphate, it is necessary to determine the residual phosphorus concentration in the solution. The concentration of polluted phosphorus is comprehensively determined by using the "Determination of Total Phosphorus in Water Quality - Ammonium Molybdate Spectrophotometry" and referring to GB11893-89 standard. The adsorption amount of the material is calculated as follows:
[0103] ×V
[0104] The solution pollutant removal rate calculation formula is as follows:
[0105] ×100%
[0106] Among them, C0 and C t (mg·L -1 ) are the initial and solution concentrations after adsorption time t, V (L) is the volume of the adsorbate solution, m (g) is the material mass, Q e (mg·L -1 ) is the adsorption amount, that is, the mass of the adsorbate adsorbed by unit mass of material, and η (%) is the pollutant removal rate in the solution.
[0107] Determination of fluorine:
[0108] The residual fluoride concentration in the solution after using the composite preparations prepared in Examples 1 to 6 and Comparative Examples 1 to 5 was measured according to the "Determination of Fluoride Ions in Water by Ion Selective Electrode Method" and in accordance with GB7484-87. The results are shown in Table 1 below:
[0109] Table 1 Summary of experimental results
[0110] project Fluoride removal rate / % Phosphorus removal rate / % Example 1 97 98 Example 2 98 98 Example 3 94 97 Example 4 97 95 Example 5 96 96 Example 6 98 98 Comparative Example 1 69 70 Comparative Example 2 79 79 Comparative Example 3 72 71 Comparative Example 4 73 73 Comparative Example 5 71 72
[0111] Data Analysis:
[0112] As can be seen from Table 1, the composite preparation for solidifying fluorine and phosphorus in phosphogypsum prepared by the present invention has a high fluorine removal rate and a high phosphorus removal rate. This is because the clay minerals are grafted and modified by maleic anhydride and polyacrylic acid-sodium acrylate, respectively, so that the porosity and specific surface area of the clay minerals are increased, and at the same time, the active groups on the surface of the clay minerals can form bonds with fluorine and phosphorus in the system, thereby increasing the removal rate of fluorine and phosphorus in the system. In addition, since the clay minerals grafted with maleic anhydride and the clay minerals grafted with polyacrylic acid-sodium acrylate are cross-linked to form a network structure, the clay minerals have a larger adsorption capacity. In addition, the use of compounded unmodified clay minerals can increase the dispersibility of the composite preparation in the system, prevent the system viscosity from being too large, and thus enable the modified clay minerals to better play their role. The three-dimensional network structure formed between the clay minerals modified by maleic anhydride and the clay minerals grafted by polyacrylic acid-sodium acrylate provides space for the unmodified clay minerals, coagulants and other small molecular active components, making the system evenly dispersed and having a larger contact area with the fluorine and phosphorus in the system, thus having a higher fluorine removal rate and phosphorus removal rate;
[0113] In addition, after the composite preparation of the present invention is used to solidify the fluorine and phosphorus in the phosphogypsum, in the resulting mixture, the phosphogypsum and fly ash, as solid wastes, act synergistically with other components in the system. The fly ash calcined at high temperature contains silicates and metal oxides, wherein the metal oxides will dissolve some metal cations when encountering acidic phosphogypsum, and at the same time, the phosphorus in the phosphogypsum will be solidified in the form of phosphate, and the fluorine in the system will form calcium fluoride with the calcium ions in the system. Since the solubility of calcium fluoride is about 10 mg / L, the treatment result can finally meet the standard.
[0114] In contrast, in Comparative Example 1, since no modified clay mineral was added to the system during the process, the final composite preparation had a poorer removal effect on fluorine and phosphorus than Example 1, both from the perspective of adsorption and from the perspective of bonding with fluorine and phosphorus. In Comparative Example 2, no clay mineral was added to the system. Although some modified clay minerals were present in the system, the modified clay minerals themselves had cross-linking and other interactions, which reduced the dispersibility of the final composite preparation. Therefore, the contact area between the composite preparation prepared in Comparative Example 2 and the fluorine and phosphorus in the system decreased, resulting in a decrease in its removal rate of fluorine and phosphorus. In Comparative Examples 3 and 4, only clay minerals grafted with polyacrylic acid-sodium acrylate or clay minerals grafted with maleic anhydride are present in the system. In this case, since there is no network structure formed by interaction in the system, the adsorption capacity of the final composite preparation is reduced compared with Example 1, and therefore the removal rate is also reduced accordingly; in Comparative Example 5, mixed clay minerals grafted with maleic anhydride and clay minerals grafted with polyacrylic acid-sodium acrylate are used to replace the mixed clay mineral modified with hydroxy iron. Compared with Example 1, the content of active groups on the surface of the composite preparation in the system is reduced, and therefore the removal rate is reduced.
[0115] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
[0116] The present invention is intended to cover all such substitutions, modifications and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum, characterized in that: The method comprises the following raw materials in parts by weight: 20-40 parts of modified clay mineral, 10-15 parts of clay mineral, 1-2 parts of coagulant, 0.1-0.6 parts of additive, 180-200 parts of deionized water, and 1.55-5.7 parts of fly ash; The modified clay mineral is a mixed clay mineral modified by hydroxy iron; The mixed clay mineral is obtained by mixing a clay mineral grafted with maleic anhydride and a clay mineral grafted with polyacrylic acid-sodium acrylate; The clay mineral is any one of montmorillonite, bentonite, diatomaceous earth, kaolinite, attapulgite and loess; The coagulant is any one of PAC-26% and PAC-98%; The auxiliary agent is a calcium hydroxide solution with a concentration of 1-2wt%.
2. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to claim 1, characterized in that: The preparation method of the modified clay mineral is as follows: Step S1. adding clay mineral to HCl solution, stirring at 75-80°C for 30-50 min, cooling to room temperature after the reaction is completed, filtering, washing with single distilled water until neutral, and drying to obtain a mixture A; Step S2. Mix the mixture A, primary distilled water and anhydrous ethanol, stir and disperse for 25-35 minutes, adjust the pH of the system to 3-4, then add KH-570, continue to stir and react for 25-35 minutes at room temperature, then adjust the pH of the system to 9-10, heat to 75-80°C, stir and react for 2-3 hours, and after the reaction is completed, filter the product, wash with ethanol 2-3 times, and then dry at 45-50°C for 5 hours to obtain a mixture B; Step S3. Mix the mixture B and 1,4-dioxane evenly, stir and disperse for 50-60 minutes, add N-vinyl pyrrolidone, maleic anhydride and N'N-methylenebisacrylamide in sequence, continue stirring for 50-60 minutes, then add azobisisobutyronitrile, react at 70-75°C for 3.5-4 hours, then add NaOH solution, stir for 1 hour, filter, wash with distilled water once until neutral, wash with anhydrous acetone 2-3 times, and vacuum dry for 6-7 hours to obtain a clay mineral grafted with maleic anhydride; Step S4. Cyclohexane and emulsifier Span80 are stirred electrically at 40-45° C. and 225-250 r / min for 25-35 min to obtain a mixture C; Step S5. Dissolve NaOH in deionized water, add acrylic acid, clay mineral and N'N-methylenebisacrylamide, stir electrically at 475-500 r / min for 50-60 min, and then add potassium persulfate to obtain a mixture D; Step S6. The mixture C is heated to 65-70° C., the mixture D is added dropwise to the mixture C, stirred at a speed of 475-500 r / min for 2-3 hours, filtered, washed with distilled water for 2-3 times, and then dried in a constant temperature drying oven at 125-150° C. for 5-6 hours to obtain a polyacrylic acid-sodium acrylate grafted clay mineral; Step S7. Add NaOH solution to FeCl3 solution, stir for 1.5-2h, add maleic anhydride grafted clay mineral and polyacrylic acid-sodium acrylate grafted clay mineral, stir for 2-3h, filter and separate the solid phase product, wash with distilled water until there is no chloride ion in the filtrate, and then dry at 125-150°C for 5-6h to obtain a modified clay mineral.
3. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to claim 2, characterized in that: The clay mineral in step S1 is a clay mineral that has passed through a 100-mesh sieve, the usage ratio of the clay mineral to the HCl solution is 8-13 g:90-110 mL, and the concentration of the HCl solution is 20%-30%.
4. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to claim 2, characterized in that: In step S2, the usage ratio of the mixture A, single distilled water, anhydrous ethanol and KH-570 is 8-13 g: 40-50 mL: 30-40 mL: 4-9 g.
5. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to claim 2, characterized in that: In step S3, the dosage ratio of the mixture B, 1,4-dioxane, N-vinyl pyrrolidone, maleic anhydride, N'N-methylenebisacrylamide, azobisisobutyronitrile and NaOH solution is 15-20 g: 150-160 mL: 10-15 g: 10-15 g: 2-3 g: 8-10 g: 10-15 mL, and the concentration of the NaOH solution is 20%-30%.
6. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to claim 2, characterized in that: The usage ratio of cyclohexane and emulsifier Span80 in step S4 is 50-55 g: 2-3 mL.
7. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to claim 2, characterized in that: In step S5, the dosage ratio of NaOH, deionized water, acrylic acid, clay mineral, N'N-methylenebisacrylamide and potassium persulfate is 0.2-0.25 g: 12-17 mL: 1.5-2.5 mL: 5-10 g: 0.2-0.3 g: 0.05-0.1 g, and the clay mineral is a clay mineral passed through a 100 mesh sieve.
8. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to claim 2, characterized in that: In step S6, the usage ratio of the mixture C and the mixture D is 50-55 mL:15-20 mL.
9. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to claim 2, characterized in that: In step S7, the dosage ratio of the NaOH solution, the FeCl3 solution, the maleic anhydride grafted clay mineral and the polyacrylic acid-sodium acrylate grafted clay mineral is 460-500mL: 140-160mL: 17-22g: 30-35g, the concentration of the NaOH solution is 0.25-0.35mol / L, and the concentration of the FeCl3 solution is 0.07-0.12mol / L.
10. A composite preparation of fluorine and phosphorus for solidifying phosphogypsum according to any one of claims 1 to 9, characterized in that: The composite preparation is used for solidifying fluorine and phosphorus in phosphogypsum.
Citation Information
Patent Citations
A method for recovering soluble fluorine in phosphogypsum
CN115784238B
Loess particle grafted copolymer adsorbent and preparation method thereof
CN106905496A
Fluorine fixing and phosphorus locking and wastewater advanced treatment system and method for ardealite slag warehouse
CN118184065A
Cited By
High-purity Ca-MOF fluorine fixing agent as well as preparation method and application thereof
CN121847549A
Phosphogypsum low-alkalinity composite phosphorus-fluorine curing agent and preparation method thereof
CN121945517A